Reply to shipment of pre-fabricated steel structure against LC no. 0000021619010057 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding reply to shipment of pre-fabricated steel structure against LC no. 0000021619010057 of BRAC University new campus project.